ANALISIS PERKEMBANGAN MOTORIK KASAR PADA MATA PELAJARAN PJOK SISWA SEKOLAH DASAR - Aldi Fuaidi Hasibuan; Seifani Fadilla; Xanana Briliyan Silalahi; Nicholas Stevenly Austin Sinaga; Estomihi Hotasi Gultom; Amansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Gross motor development is an important aspect of elementary school students' growth and development, supporting their motor skills, physical fitness, and daily activities. This skill involves the use of the body's large muscles in various motor skills, such as walking, running, jumping, throwing, catching, and maintaining balance. Physical Education, Sports, and Health (PJOK) plays a crucial role in developing students' gross motor skills through various structured physical activities. This study aims to describe the gross motor development of elementary school students in PJOK learning based on published research results. This study used a literature review method with a library research approach. Data were obtained through a search of scientific articles on Google Scholar using the keywords "student motor development," "gross motor skills," and "gross motor skills in PJOK learning." Nine relevant national journals were analyzed using content analysis techniques. The results of the study indicate that elementary school students' gross motor skills are generally in the adequate to good category. However, this development is not evenly distributed across all aspects of motor skills, especially in skills requiring complex motor coordination. Furthermore, gross motor development is influenced by various factors, such as physical activity, the environment, movement experiences, facilities and infrastructure, and the learning model implemented by teachers. Therefore, varied, innovative, and student-centered physical education (PJOK) learning is necessary to optimize gross motor development in elementary school students.